The Effectiveness of Targeted Electrical Stimulation via Cochlear Implant on Tinnitus-Perceived Loudness - Di Nardo, Walter; Di Cesare, Tiziana; Tizio, Angelo; Paludetti, Gaetano; Fetoni, Anna Rita (Frontiers in Neuroscience, 2022)
Introduction: The cause of tinnitus improvement in cochlear implant (CI) users is not understood. On the basis that a spatially limited dysfunction in the auditory pathway could cause tinnitus, we used single-channel stimulation to evaluate any variation of tinnitus perceived loudness and identify the cochlear regions involved. Methods: It was an observational prospective case-crossover study. After the first mapping, 21 adults with unilateral CI and chronic tinnitus expressed their tinnitus loudness based on the VAS score (0-10) at baseline (L0), during a 10 second single-channel stimulation with C-level of electric current (L1) and 30 minutes after CI activation (L2). Tinnitus reduction [RT = (L0 – L1) x 100 / L0] > 50% was considered significant.. VAS outcomes were compared between baseline (L0) and (each) single-channel stimulation (L1), to find the channel with the greatest RT (suppressive channel-SC), whose frequency range revealed the cochlear region involved. Seven patients with asymmetric hearing loss underwent the pitch-matching test to identify the actual frequency evoked by the SC. We compared selective (L1) and non-selective (L2) intracochlear stimulation using paired T-test. Preoperative THI score was compared to those at 1, 6 and 12 months with paired T-tests to evaluate long-term tinnitus perception. Results: We observed a significant reduction of tinnitus loudness during the experimental procedure L0(6.4±2.4) vs. L1(1.7±2.7), p=0.003. 15/21 patients (71.4%) had a significant (RT>50%) and selective improvement, reporting a mean L1 of 0.4±2.0 (p=0.0001). In 10/15 (66.6%) patients the SC was in the apical turn, within 1000 Hz; in 5/15 patients (33.4%) within 4000 Hz. The cochlear region 125-313Hz was the most affected by tinnitus improvement (p=0.0074). Targeted stimulation was more effective than non-selective stimulation L1 vs. L2 (4.3±2.5), p=0.0022. In 3/7 patients the perceived pitch did not fall within the SC frequency ranges. All patients with selective attenuation described tinnitus as monotone. Patients with non-selective attenuation had polyphonic tinnitus and better THI results after one year. Conclusions: Targeted intracochlear electrical stimulation improved chronic tinnitus perception especially in monotone tinnitus and the apical region was mainly involved. Our results provide new insights into pathophysiological mechanisms of tinnitus and targets for innovative therapeutic strategies.